Silverwork, pearls and businesses in the first half of the 16th century. Alonso de Oviedo and his central role in American and commercial Seville (2021)
With this work, we will approach the complex and dynamic historical context of the first half of 16th-century Seville, when commercial and financial activity acquired dimensions never seen before in Europe thanks to the emerging possibilities of transactions in the New World. The protagonists of this vital impulse, the Spaniards as well as those from other points in the continent, are only partially known. Day after day, new examples of the «man of business with the Indies» appear. Alonso de Oviedo, who is analysed here, helps us to understand in a broader way the temporal, human and economic space indicated. His profile goes beyond the clichés of this typology, as it adds to his dedication to business, an artistic activity very much connected with the economic development mentioned, such as the art of silverwork, also explored in these lines. The relationship with the businesses of pearls and seed pearls fits within one of the chapters of most interest in the European society of the time, associated with luxury and the mystery of faraway lands and seas. The starting point of this research is a large number of unknown documents from the Archivo General de Indias (General Archive of the Indies) and Archivo Histórico Provincial (Provincial Historical Archive), both from Seville.